The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00423-009-0563-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy-based hemostatic devices in laparoscopic adrenalectomy

Abstract: Obesity (BMI > 30) and large masses do not contraindicate laparoscopic adrenalectomy. Left adrenalectomies bleed more and have a higher morbidity. Hemostatic device choice is up to surgeon's preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…There are some studies in the literature comparing Ligasure and Ultracision in laparoscopic colectomy 9,12,13 and adrenalectomy 14 . We think that the present study is the first to address this topic in laparoscopic splenectomy.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…There are some studies in the literature comparing Ligasure and Ultracision in laparoscopic colectomy 9,12,13 and adrenalectomy 14 . We think that the present study is the first to address this topic in laparoscopic splenectomy.…”
Section: Introductionmentioning
confidence: 76%
“…10,11 There are some studies in the literature comparing Ligasure and Ultracision in laparoscopic colectomy 9,12,13 and adrenalectomy. 14 We think that the present study is the first to address this topic in laparoscopic splenectomy. The aim of the present study was to compare the effectiveness of Ligasure alone or Ligasure and Ultracision together in LS.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The most recent article published about new hemostatic devices in laparoscopic adrenalectomy was conducted in 2010 by Sartori et al 6 They reported their experience of 46 patients undergoing laparoscopic adrenalectomy with EBVS or US: the authors failed to demonstrate any differences in the outcomes between the two groups and concluded that hemostatic device choice is up to surgeon's preference. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the present study, the operative time in US group was comparable with those reported in the literature. 6 Valeri et al 4 reported a significantly reduced operative time with the use of US, but this might be due to their rare use of hemostatic clips for the adrenal vein.…”
Section: Discussionmentioning
confidence: 99%